Phylogeny and historical biogeography of Hydrophyllaceae and Namaceae, with a special reference to Phacelia and Wigandia. Issue 8 (16th November 2020) - Vasile, Maria-Anna; Jeiter, Julius; Weigend, Maximilian; Luebert, Federico
Abstract : This study aimed to examine the systematic position of South American species of Phacelia (Hydrophyllaceae) and Wigandia (Namaceae) and the historical biogeography of Hydrophyllaceae and Namaceae using molecular dating and ancestral area reconstruction. To this end, we constructed two datasets, one with a plastid ( ndhF ) and one with a nuclear marker (ITS), using previously published and newly generated sequences. We inferred the phylogeny of Hydrophyllaceae and Namaceae implementing both likelihood and Bayesian methods. We also estimated divergence times and ancestral areas for all major clades using a relaxed Bayesian uncorrelated molecular clock and the dispersal-extinction-cladogenesis (DEC) approach, respectively. The South American representatives of Phacelia are placed in three different clades of the genus and two colonizations of South America by North American species took place in the Miocene and at least one in the late Pliocene. Wigandia forms a well-supported monophylum with interspecific relationships partly unresolved. Within Namaceae a colonization of South America by North American species occurred during the Oligocene–Miocene transition. The MRCA of Wigandia was distributed in North and Central America in late Oligocene. Long-distance dispersal may have been necessary for the colonization of South America by Namaceae during the Oligocene–Miocene transition, when North and South America were not connected.